Pengaruh Kompensasi terhadap Kepuasan Kerja Guru: Studi Empiris pada SD Negeri di Nagari Kinari Kecamatan Bukit Sundi - Nurhayati Nurhayati; Rasidah Nasrah; Yunus Surya (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
A teacher's attitude toward their work or teaching is a key indicator of their job satisfaction, and compensation which includes pay, bonuses, and other forms of appreciation is a way for the organization to recognize the contributions of its employees, all of which have an impact on job satisfaction. The purpose of this study is to examine how teacher job satisfaction is impacted by compensation in public elementary schools in Nagari Kinari, Bukit Sundi District. Based on factors including gender, age, education level, and duration of service, the study's sample consisted of 36 respondents. The t-test score for the compensation variable was higher than the t-table (3.906 > 2.03452), indicating that teacher job satisfaction is impacted by compensation. The findings of the determination coefficient test indicate that there is a 36.5% relationship between the pay variable (X2) and the dependent variable of teacher job satisfaction (Y). The study's findings indicate that managing compensation policies needs to be done in a sustainable and planned manner. Teachers will feel more valued, supported, and appreciated for their professionalism if they are paid more. Higher job satisfaction will follow, which may lead to better performance and a favorable effect on students' academic achievement in schools.